2009
DOI: 10.1002/em.20490
|View full text |Cite
|
Sign up to set email alerts
|

Increased consumption of wheat biofortified with selenium does not modify biomarkers of cancer risk, oxidative stress, or immune function in healthy Australian males

Abstract: Increased intake of selenium (Se) may reduce the risk of degenerative diseases including cancer but excessive intake may be toxic. Wheat is a major source of dietary Se in humans. However, the effect of Se from wheat that is agronomically biofortified with Se on biomarkers of human health status is unknown. This study aimed to investigate whether improving Se status, by increased dietary intake of Se‐biofortified wheat, affects biomarkers of cancer risk, cardiovascular disease risk, oxidative stress, and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 46 publications
1
26
0
Order By: Relevance
“…By contrast, several other studies showed that cancer-relevant biomarkers of oxidative stress were unchanged by diet. For instance, increased consumption of selenium-rich food and subsequent increase in blood Se concentrations did not affect biomarkers of oxidative stress in healthy Australian males (387). No differences in the DNA and lipid oxidative damage markers and antioxidant capacity between intervention groups of healthy, nonsmoking men receiving 2, 5, or 8 servings/day of vegetables and fruit were found (45).…”
Section: The Limitations Of Oxidation Markers In Usementioning
confidence: 89%
“…By contrast, several other studies showed that cancer-relevant biomarkers of oxidative stress were unchanged by diet. For instance, increased consumption of selenium-rich food and subsequent increase in blood Se concentrations did not affect biomarkers of oxidative stress in healthy Australian males (387). No differences in the DNA and lipid oxidative damage markers and antioxidant capacity between intervention groups of healthy, nonsmoking men receiving 2, 5, or 8 servings/day of vegetables and fruit were found (45).…”
Section: The Limitations Of Oxidation Markers In Usementioning
confidence: 89%
“…Against this, Wu et al [23] did not find any beneficial effects in human Applied and Environmental Soil Science 3 Australian males who consumed a supplementary Se diet with biofortified wheat (193 m/L). In these individuals, the beneficial effects were tested through biomarkers of cancer and cardiovascular diseases.…”
Section: Importance Of Selenium In the Human Dietmentioning
confidence: 94%
“…They reported that consumption of 20 g of biofortified lentil can supply all of the recommended daily allowance of Se. Consumption of Sebiofortified wheat was found to increase plasma Se concentration from a baseline level of 122 to 192 µg L -1 [135]. However, improvement of Se status by consumption of Se-biofortified wheat did not substantially modify the selected biomarkers of degenerative disease risk and health status in selenium replete cohort of healthy older men in South Australia.…”
Section: Agronomic Biofortificationmentioning
confidence: 82%